KAJIAN DAMPAK SUBSTITUSI KACANG TUNGGAK PADA KUALITAS FISIK DAN KIMIA TAHU (Jurnal Teknologi Pangan, 2013)
Tofu is a soy protein product with a protein coagulation process at its soelektric point. Soy protein precipitation was  range between pH 4.5 which is the point isoelektris soybean globulin. In  efforts  to  reduce  the  use  of  soy  in  the  making  tofu, cowpea  is  one  source  of  vegetable protein  had  a  good  nutritional  composition  of  one  protein,  vitamain  B,  vitamin  C  and  fiber. Cowpea  can be used as raw material of tofu. The use of citric acid as a coagulant will give a high yield in tofu. This study aims to know the effect of the proportion of cowpea and citric acid concentration  on the  quality  of  physical,  chemical  and  organoleptic while  they knew  the  best treatment  combination.This  research  used  Completely  Randomized  Design  (CRD)  which  are arranged  in  factorial  which  consist  of  two  factors  and  repeated  3  times.  Factor  I  is  the proportion of cowpea 20%, 30%, 40% and the second factor is the concentration of citric acid solution  is  10.5%,  11.5%,  12.5%.The  best  results  are  obtained  on  the  proportion  of  20% cowpea  treatment  with    citric acid  concentration  of  12.5%.The resulting was in  a  yield  of 158.767%,  moisture  content of  80.131%,  protein  content  of  9.191%, texture  of 0.088  mm  / gr.dtk  and  organoleptic  value  by  the  number  of  149  flavor rank,  color of  125.5.and  texture of 147.5Key words : Tofu, Cowpea, citric acid